Saving-Enhanced Memory - Storm, Benjamin C.; Stone, Sean M. (Psychological Science, 2015)
With the continued integration of technology into people’s lives, saving digital information has become an everyday facet of human behavior. In the present research, we examined the consequences of saving certain information on the ability to learn and remember other information. Results from three experiments showed that saving one file before studying a new file significantly improved memory for the contents of the new file. Notably, this effect was not observed when the saving process was deemed unreliable or when the contents of the to-be-saved file were not substantial enough to interfere with memory for the new file. These results suggest that saving provides a means to strategically off-load memory onto the environment in order to reduce the extent to which currently unneeded to-be-remembered information interferes with the learning and remembering of other information.